Метод Монте-Карло в атмосферной оптике - Марчук Г. И. Гурий Иванович; Михайлов Г. А. Геннадий Алексеевич; Назаралиев М. А. Магомедшафи Ахмедович; Дарбинян Р. А. Размик Арамович (Новосибирск, Наука, 1976)
Загл. указано на пер.